Returning an employee to work on the basis of a court judgment - Antić, Aleksandar; Ćorac, Sanda (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
In case of illegal termination of employment, during court proceedings, the employee can request the court to oblige the employer to return him to work. However, reinstatement of the employee is not mandatory. The reintegration of an employee into the work process, in case of illegal termination of employment, entails numerous legal and practical problems. Namely, the Labor Law, but also other laws, do not provide for the behavior of the employer if it is impossible to carry out the return to work due to the occurrence of certain objective circumstances, and it is also not provided for the possibility that the employee who has been returned to work can, within a certain period, replace this right with monetary compensation, if after returning to work he did not adapt to the changed work environment or was employed by another employer, immediately before the judgment was passed. With the aim of analyzing the problems related to the return to work of an employee based on a court judgment and considering related theoretical and practical issues, the presentation is divided and consists of two parts. The first part of the paper analyzes the provisions of the Labor Law regarding the legal consequences of illegal termination of employment, while the second part of the paper discusses the essential features of the provisions of the Law on Enforcement and Security, which regulate enforcement for the purpose of returning the employee to work.
Keywords: illegal employment relationship; consequences of illegal termination of employment relationship; execution procedure for returning the employee to work